TECHNOLOGICAL PROGRESS AND HUMAN DEVELOPMENT: EVIDENCE FROM INDONESIA - Muchdie, M.; Nurrasyidin, M. (Universitas Muhammadiyah Yogyakarta, 2019)
This paper examined direct and indirect impact of technological progres on human development, with income disparities and povertyas moderating variables. Except data on technical progress, all data were collected from National Statistics Agency. A path model of analysis was empolyed to examine direct and indirect impacts.There were four paths to be analysed: direct impact (Path-1: P41) and indirect impacts : (Path-2: P43 x P31, Path-3: P43 x P32 x P21 and Path-4 : P42 x P21). Four hypothesis had been tested.The results showed that impact of technological progress on human development were negative, both direct and indirect.